A bibliometric study of the scientific publications that use facial emotion recognition tests - Jeanneret, Graciela; Oña, Astrid; Rego, Pamela; Vaiman, Marcelo; Pereno, Germán (Anales de Psicología / Annals of Psychology, 2014)
This work is in line with the evolutionary theory, which supports the existence of basic and universal emotions, stress the study of his facial expression and his recognition. Though the development of FACS in 1978 for Ekman motivated the creation of facial emotion recognition test, there is not in Argentine test that measure the above mentioned ability. The aim of this study was carry out a bibliometric study of the scientific publications that use facial emotion recognition tests published between 1976 and August, 2011. This process of systematizing offers visibility on the current condition of the science in relation to the above mentioned tests, constituting the first step for the development of a local test. In effect, there were analyzed the productivity, scientific collaboration, h-index and matter analysis indicators. These demonstrated a systematic growth increasingly in researches in facial emotions recognition. These studies use photographs as the POFA and the JACFEE in adult population of both male and female sexes, becomes more relevant the study of pathologies, mainly the schizophrenia. These results, in turn, will be able to be in use as base for successive research projects that contribute to the progress of the science.